An exact routing optimization model for bio-waste collection in the Brussels Capital Region. (30th November 2021) - Lavigne, Carolien; Beliën, Jeroen; Dewil, Reginald
Abstract: This paper presents a routing optimization model for a wide range of waste collection problems which allows for multiple depots with homogeneous, capacitated vehicles, intermediate stops at multiple processing facilities, and multiple pick-ups per waste collection location. By minimizing collection routing and vehicle investment costs, the model estimates the total transportation costs for a given network design and waste volumes to be collected at different demand points. The number of feasible routes is severely reduced by restricting the number of subsequent pick-up location visits. The model's use is illustrated through assessing four future, realistic bio-waste collection scenarios of the Brussels Capital Region (BCR). The scenarios differ with respect to assumptions on future collection rates, joint versus separate collection of food and green waste, and number and locations of processing facilities. The results show that the highest cost reduction can be achieved through joint collection of food and green waste combined with three composting locations. Moreover, we found that introducing multiple processing facilities significantly increases the complexity of the waste collection problem. Highlights: Exact model for a general waste collection problem. Evaluating future waste collection infrastructure scenarios. Joint collection can reduce bio-waste collection costs with up to 31%. Cost reductions if treatment locations are spread over the collection area. Introducing multiple treatment locations significantly increases complexity.